Penemuan dan Inovasi: Sumber Belajar Berbasis Al-Qur’an - pajarni; Zharfa Hazrina, Putri; Oktafia, Anisa; Tashakurin, Awaliya; Hasanah, Aulia; Yusriyah (CV Kalimasada Group, 2024)
This article explores how the Qur'an encourages educational innovation and scientific discovery through various verses that emphasize the importance of science and critical thinking. Verses such as QS. Al-'Alaq: 1-5 and QS. Al-Mujadilah: 11 invites humans to read, study and respect knowledge, and recognize the greatness of God through knowledge. Education in the Koran aims to shape human character and deepen recognition of the greatness of God. The next discussion connects the scientific principles contained in the Koran with discoveries and innovations in modern science. Verses such as QS. Al-Hadid: 25 which discusses iron and QS. Al-Hijr: 22 on genetics shows that the Qur'an has relevance to contemporary scientific discoveries. This shows that the principles taught in the Koran can inspire progress in various fields of science. Finally, this article highlights how the Koran inspires technological innovation, especially in the field of transportation. Verses such as QS. An-Nahl: 8 and QS. Al-Mulk: 19 touches on advances in technology and transportation, showing that the Qur'an encourages humanity to continue to innovate for the welfare of the people and the preservation of the earth. In conclusion, religious teachings and science can go hand in hand, and the Qur'an encourages humanity to make discoveries and innovations that are beneficial for the common good. The research method used in this journal article is a qualitative method with a focus on the type of narrative or library research.